Pharyngeal airway changes following maxillary expansion or protraction: A meta‐analysis. (28th December 2017) - Lee, W.‐C.; Tu, Y.‐K.; Huang, C.‐S.; Chen, R.; Fu, M.‐W.; Fu, E.
Abstract: The aim of this meta‐analysis was to investigate the changes in airway dimensions after rapid maxillary expansion (RME) and facemask (FM) protraction. Using PubMed, Medline, ScienceDirect and Web of Science, only controlled clinical trials, published up to November 2016, with RME and/or FM as keywords that had ≥6 months follow‐up period were included in this meta‐analysis. The changes in pharyngeal airway dimension in both two‐dimensional and three‐dimensional images were included in the analysis. Nine studies met the criteria. There are statically significant changes in upper airway and nasal passage airway in the intervention groups as compared to the control groups, assessed in two‐dimensional and three‐dimensional images. However, in the lower airway and the airway below the palatal plane, no statistically significant changes are seen in 2D and 3D images. RME/FM treatments might increase the upper airway space in children and young adolescents. However, more RCTs and long‐term cohort studies are needed to further clarify the effects on pharyngeal airway changes.